SIMULTANEOUS REVERSE-PHASE ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF GRAZOPREVIR AND ELBASVIR - S, Madhavi; Rani A, Prameela (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to develop and validate rapid, specific, sensitive, and precise reverse-phase ultra performance liquid chromatography (RP-UPLC) method for the quantitative determination of grazoprevir and elbasvir, as there are no official monograph and no analytical method by UPLC. Methods: Chromatographic separation was achieved on a Waters Acquity UPLC HSS C18 (2.1 mm × 100 mm, 1.8 micron) column with a 45:55 (v/v) mixture of 0.1% orthophosphoric acid (pH 2.8) and acetonitrile as a mobile phase, thermostated at 30°C with a short run time of 3.0 min. Results: The retention times were 0.73 and 1.29 min for grazoprevir and elbasvir, respectively. Quantification is achieved with TUV detection at 254 nm over the concentration range of 25–150 μg/ml for grazoprevir and for elbasvir 12.5–75 μg/ml, with a correlation coefficient of 0.999 and 0.999, respectively. The developed method was validated according to the International Conference on Harmonization (ICH) guidelines with respect to linearity, accuracy, precision, specificity, and robustness. Forced degradation study was extended out under acidic, alkaline, oxidative, photolytic, and thermal conditions to demonstrate the stability-indicating capability of the developed UPLC method. The degradation products were well resolved from the main peak, thus proved the stability-indicating power of the method. The results of the analysis were validated statistically. Conclusion: The method is precise, accurate, linear, robust, and fast. The short retention time allows the analysis of a large number of samples in a short period of time and, therefore, should be cost-effective for routine analysis in the pharmaceutical industry.